(3QSGdI aj cjajI GdbVGjG HGdfLhe hGdMce Ydi GdehGdjOs - (3jMji Hf eMeO Hf CHj GdTcQ, eMjj GdOjf, CHh GdaJM, hjYQa HGdMcje GdeZQHj , GHf CHj GdoqTrcQ , J fMh (B680 (3g`s
(3ChdgG (B:s
, (3gPg QSGdI CdagG ai cjajI GdbVGjG HGdfLhe hGdMce Ydi GdehGdjO heG JbJVjg CMhGd GdSGFd eeG EfJNHg GdeMOKhf ef cdGe GdMceGA GdGbOejf s
(3BNQgG (B:s
(3heJi cGfJ GdfMhS CQHGH GdChJGO hgj ajgG aJMgG CgdgG ddYOhd hedcJgG dg hajeG PcQfG caGjg Ke QSGdI GdMce Ydi GdeSGFd GdfLhejI s
(3GdfSNI HgG MhGTs
(3HBNQgG fbhds
(3HgG fXGe GdJYbjHI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs